2020
DOI: 10.3390/antibiotics9020093
|View full text |Cite
|
Sign up to set email alerts
|

Modified Aminoglycosides Bind Nucleic Acids in High-Molecular-Weight Complexes

Abstract: Aminoglycosides represent a large group of antibiotics well known for their ability to target the bacterial ribosome. In studying 6”-substituted variants of the aminoglycoside tobramycin, we serendipitously found that compounds with C12 or C14 linear alkyl substituents potently inhibit reverse transcription in vitro. Initial observations suggested specific inhibition of reverse transcriptase. However, further analysis showed that these and related compounds bind nucleic acids with high affinity, forming high-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Collectively, all results suggested that amphiphilic aminoglycosides derived from neamine are interesting molecules for the development, in the future, of new antibiotics targeting bacterial membranes and/or tools for the study of the dynamics of bacterial membranes. How these activities could be extended to antiviral [70] or antifungal [71][72][73] activities and what are the strategies to block LPS biogenesis [74] should also be explored and could open new avenues based on the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, all results suggested that amphiphilic aminoglycosides derived from neamine are interesting molecules for the development, in the future, of new antibiotics targeting bacterial membranes and/or tools for the study of the dynamics of bacterial membranes. How these activities could be extended to antiviral [70] or antifungal [71][72][73] activities and what are the strategies to block LPS biogenesis [74] should also be explored and could open new avenues based on the current work.…”
Section: Discussionmentioning
confidence: 99%
“…NEO was found to be the most efficient cleaving AG drug, followed by the AAG 76 (Figure 18) resulting from the conjugation of the NEA core to the nucleic base adenine (EC 50 = 0.09 and 0.15 µM, respectively, and EC 50 (NEA) = 0.9 µM). The study of 6"-substituted variants of TOB, derivatives with C-12 or C-14 linear alkyl substituents, revealed a potent inhibition of reverse transcription in vitro, which was related to nucleic acid binding with high affinity and the formation of high-molecular weight complexes [155]. Stable complex formation was observed with DNA or RNA in single-or double-stranded form, suggesting that the formation of micelles and/or vesicles with surface-bound nucleic acids may be a useful tool to localize nucleic acids to surfaces or deliver nucleic acids to cells or organelles.…”
Section: Some Particular Effects Of Aags On Dna and Rnamentioning
confidence: 99%
“…The chemical modification of already existing antimicrobials has achieved some success, such as the chemical modifications introduced in the β-lactam ring of penicillin to prevent its hydrolysis by penicillinases. Ying et al have synthesized aminoglicosides variants containing different alkyl substituents [7]. The authors report that those variants containing C 12 or C 14 linear alkyl substituents were serendipitously found to strongly inhibit reverse transcriptase.…”
mentioning
confidence: 99%
“…The authors report that those variants containing C 12 or C 14 linear alkyl substituents were serendipitously found to strongly inhibit reverse transcriptase. The authors show evidence that these compounds act by binding nucleic acids with high affinity, forming high-molecular-weight complexes [7]. The compounds were predicted to be useful for nucleic acids localization or in the delivery of nucleic acids to cells or cellular compartments [7].…”
mentioning
confidence: 99%